Design and analysis of an adaptive hybrid structure of linearly interconnected scissor-like and cable bending-active components. (1st August 2019) - Phocas, Marios C.; Alexandrou, Kristis; Athini, Stella
Highlights: A system of two components alternatingly linearly interconnected is developed. Scissor-like elements are connected with cable bending-active members in pairs. In the form-found state the scissor-like elements' joints are locked. Coupling cables increase the stiffness of the bending-active members. The system enables form flexibility and adaptability. Abstract: The development of transformable structures in architecture is primarily based on the reduction of self-weight, construction volume and technical complexity, so as to achieve reconfigurability and provide efficient kinematics in terms of shape transformations and deformations. Along these lines, the current paper refers to the design and analysis of an adaptive structure of two components alternatingly linearly interconnected; namely, scissor-like elements (SLEs), and inversely curvilinear cable bending-active members in pairs. Initially, the study investigates parametrically the geometrical configurations of the proposed structural system as to the location of the SLEs joint and the relative lengths of the elastic members in pairs. The subsequent Finite-Element Analysis (FEA) of nine selected system configurations includes their form-finding and vertical loading. In the respective form-found state, the central joints of the SLEs are locked via electromagnetic brakes, and the coupling cables are introduced to the bending-active members. The proposed structure aims at increasing related transformation capabilities, form flexibility and adaptability, on the basis of the two components' contribution.